Design of Mine-used Wireless Roof Pressure Sensor Based on CC2530 - WU Yao-ming; LOU Hua-ping; ZHANG Guo-liang (Gong-kuang zidonghua, 2012)
In view of problems of easy to be broken of transmission line and difficult maintenance of wired roof pressure sensor, a design scheme of wireless roof pressure sensor based on CC2530 was proposed, hardware components and workflow of the sensor were introduced. The sensor can process data collected by pressure transmitter and then transmit the data to wireless monitoring substation through antenna, so as to realize monitoring for hydraulic support and single prop on fully mechanized coal face. The test result showed that the sensor has high wireless transmitting power, good receiving sensitivity and reliable quality of signal modulation.